Teaching effectiveness in the utilization of Montessori approach in early childhood basic science learning in Ika South Local Government Area (LGA) in Delta State - Henrietta Ifeanyichukwu Nwabuwe; Mercy Afe Osagiede (Center for Humanities and Innovation Studies, 2023)
Most learners find science challenging, which may be because of the methodology used in the early years that presents it as difficult and abstract. On the other hand, the Montessori Method uses a hands-on approach to teaching science from the early years. This study, therefore, looks at the effect of the teachers' utilization of the Montessori approach to early childhood education in Ika South Local Government Area (LGA) of Delta State, Nigeria. Two research questions and hypotheses were raised. The research design adopted for the study was a descriptive, pre-test, post-test, quasi-experimental method used to test the differences between the pupils' learning experiences in the two groups. The Taro Yamane formula was used to get the sample size, and a stratified random sampling technique was used to select 77 teachers and 40 nursery pupils, comprising ten each in experimental and control groups, in two schools in Ika South LGA of Delta State. The instruments to be used for this study will be self-designed multiple-choice achievement test questions in early years' science and four-point Likert-type self-structured questionnaires. The result indicates that teachers' knowledge and utilization of the Montessori approach to teaching pre-primary science is more effective than the conventional teaching method. Some suggestions were made for the way forward